Flowering Nature of Dendrocalamus Longispathus (Kurz) Kurz with Notes on Seedling and other Planting Materials for Raising Plantation - Banik, Ratan Lal (Indian Forester, 2015)
Dendrocalamus longispathus (Kurz) Kurz is a very useful bamboo species naturally growing in the forests of north east India and neighbouring countries. The natural stock of the species is getting depleted and availability has also been decreasing alarmingly in Tripura, Mizoram and Chittagong Hill Tracts due to high demand and recent sporadic to gregarious flowering. The species distribution in local forests, behaviour of flowering clumps, inter seeding period (flowering cycle), seed ripening, raising of seedling have been studied and reported. Further highlighted the utilization of different types of planting materials and mentioned the key steps in plantation raising to assist the restocking work of this species.